Prolonged release urea powder system with potential use in sustainable agriculture - Echevarría- Hernández, Anayza; Wong- Corral, Francisco Javier; Borboa-Flores, Jesús; Rodríguez-Félix, Francisco; Del Toro- Sánchez1, Carmen Lizette; García Hernández, José Luis (Ecosistemas y Recursos Agropecuarios, 2020)
With the aim of reducing nitrogen losses in the soil, a prolonged release system (SLIP) of urea powder encapsulated in a wheat gluten matrix was studied as a sustainable alternative for use in agriculture. SLIP was characterized using the techniques: Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FT-IR) and Thermogravimetry (TGA). Subsequently, the kinetics of urea release in water were evaluated. Very porous structures were obtained and the existence of interactions through hydrogen bonds between urea and gluten proteins was confirmed and the thermal stability of SLIP was observed. The kinetics showed a rapid release of urea (38%) in the first 10 minutes, reaching the diffusion equilibrium (86.35%) at 36 hours, respectively. Urea SLIP has the potential characteristics to be used as a sustainable alternative for agriculture.